The use of multi‐frequency acquisition to significantly improve the quality of fibre‐optic‐distributed vibration sensing. (23rd February 2018) - Hartog, A.H.; Liokumovich, L.B.; Ushakov, N.A.; Kotov, O.I.; Dean, T.; Cuny, T.; Constantinou, A.; Englich, F.V.
ABSTRACT: Unlike conventional sensors that measure the passage of seismic waves at a single position, distributed vibration sensing systems, also known as distributed acoustic sensing systems, detect the passage of seismic waves by averaging a measurement of strain over a section of fibre‐optic cable. Distributed vibration sensing systems work by transmitting pulses of light down the fibre and measuring the phase of the Rayleigh backscatter. At random positions along the fibre, however, fading occurs; this is where the amplitude of the backscattered signal is very small due to cancellation of the scattered electric fields, resulting in anomalously noisy traces in a common source gather. This paper addresses the problem of fading in a particular form of distributed vibration sensors: a new optical arrangement of the instrumentation is described that allows the measurement to be carried out quasi‐simultaneously at multiple optical interrogation frequencies. The interrogation frequencies are chosen to be sufficiently different that their fading properties are distinct and the diversity thus obtained is used to aggregate the data obtained to substantially reduce the noise caused by fading. As well as reducing the effects of fading, the aggregation of the independent results can also help to reduce the overall noise of the measurement and improve the linearity of the distributed vibration sensing system.